Minimnya Literasi Budaya dan Kewargaan Dapat Mereduksi Nilai Karakter Kebangsaan - Annisa Dwi Hamdani; Dinie Anggraeni Dewi; Rizky Saeful Hayat (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This research aims to provide a clear picture regarding the lack of cultural and civic literacy which can reduce the value of national character. Indonesia is a country that has a diversity of cultures, religions, customs and so on. The developments of the times and technology that have occurred have made it easy for foreign culture to enter and be absorbed by society, this has caused quite a few Indonesian people to shift their lifestyle to follow foreign and alien cultures to their own culture. This research uses descriptive qualitative methods by collecting data from library sources. The results show that the implementation of cultural and civic literacy in Indonesia is still relatively low, which can reduce national character values such as religiosity, nationalism, independence, the spirit of mutual cooperation and integrity. Therefore, it is necessary to increase public awareness and the active role of education to increase cultural and civic literacy in order to optimize national character values.